Расчет характеристик рентгеновских установок - Orobinskyi, A. N. (PE "Politekhperiodika", Book and Journal Publishers, 2015)
Actuality of this work is related to human radiation safety during tuning and regulation of X-ray devices in the process of their development and production. The more precise the calculations for the device are, the less time is required for its tuning and regulation, and thus people are less exposed to radiation. When developing an X-ray device, it is necessary to choose an X-ray tube and filters taking into account the application domain of the device. In order to do this, one should know anode voltage, X-ray tube anode current, material and thickness of filters, i.e. to calculate these characteristics at the set quality of X-ray radiation. The known published studies do not give any solution to this problem.The scientific novelty of this work is that it establishes the interdependence between main characteristics of the X-ray device: the function of the device defines the quality of X-ray radiation (mean photon energy and air kerma power); mean photon energy depends on the X-ray anode tube voltage and spectral resolution; air kerma power depends on anode tube voltage, current of X-ray tube anode, spectral resolution, thicknesses of the filters and their materials; spectral resolution depends on thicknesses of filters and their materials; thickness of filters depends on the material of the filter (the linear coefficient of weakening of X-ray radiation). Knowledge of interdependence of basic characteristics of the X-ray devices allowes developing simple algorithm for their calculation at the values of homogeneity coefficient from 0,8 to 1, which makes it possible to choose an X-ray tube and filters with the purpose of obtaining X-ray radiation of the set quality.